Compositions comprising a monomer having a carboxylic acid group, a monomer having a hydroxyl group, a cycloalkyl monomer, and a crosslinker, and related articles and methods
Patent Information
- Application Number
- CN202180085558.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-17
- Filing Date
- 2021-12-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-17
Smart Images

Figure CN116648488B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 127,035, filed on December 17, 2020, the disclosure of which is incorporated herein by reference in its entirety. Background Technology
[0003] Adhesives are known to be used to bond one substrate to another, such as bonding metal to metal, metal to plastic, plastic to plastic, and glass to glass. Structural adhesives are an attractive alternative to mechanical joining methods such as riveting or spot welding because they distribute load stress over a larger area rather than concentrating it at a few points. Structural adhesives also produce cleaner and quieter products because they dampen vibrations and reduce noise. Furthermore, structural adhesives can be used to bond a variety of materials, sometimes without requiring extensive surface preparation.
[0004] Crosslinking agents that can be used in certain adhesive compositions are described in U.S. Patent Nos. 4,605,712 (Mueller et al.) and 4,447,493 (Driscoll et al.), and U.S. Patent Application Publication Nos. 2016 / 0137893 (Sherman et al.), 2012 / 0139138 (Samuel et al.), 2017 / 0135911 (Craig et al.), and 2020 / 017720 (Liu et al.). Certain acrylic adhesives reported to have high strength or high glass transition temperatures are described in International Patent Application Publication No. WO2019 / 012088 (Hajji et al.), Japanese Patent Application JP2016155892 published September 1, 2016, and Chinese Patent Application CN104449418 published March 25, 2015. Summary of the Invention
[0005] This disclosure provides a composition that can be used, for example, as a sealant or adhesive (e.g., a structural adhesive). In one aspect, this disclosure provides a composition comprising: an acrylic monomer containing a cycloalkyl group having up to 12 carbon atoms, an acrylic monomer having a carboxylic acid group, an acrylic monomer having a hydroxyl group, and a compound consisting of a divalent segment L and at least two X groups. The divalent segment L is represented by the following formula:
[0006]
[0007] Each divalent segment L is directly bonded to:
[0008] i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group.
[0009] ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or
[0010] iii) A secondary N atom, which is directly bonded to another divalent chain segment L or X group;
[0011] And a tertiary N atom, which is directly bonded to p another divalent segment L and (2-
[0012] p) X groups, where p is 0, 1 or 2.
[0013] In the bivalent chain segment L, each R 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1 At least some of the groups are -CH2-CH2-CH2-CH2-. Each n independently represents a positive integer, and each X group is independently represented by the following formula:
[0014] CH2=C(R)-C(O)-OVWC(O)-,
[0015] Each R is independently hydrogen or methyl, and each W is independently O, S, or NR. 2 , where R 2 The group is hydrogen or an alkyl group having up to 4 carbon atoms, and each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group. Based on the total weight of the acrylic functional compound in the composition, an acrylic monomer containing a cycloalkyl group having up to 12 carbon atoms is present in an amount of at least 16% by weight.
[0016] In another aspect, this disclosure provides an adhesive comprising the composition disclosed herein, which is at least partially cured with a free radical initiator.
[0017] In another aspect, this disclosure provides an article of manufacture that is bonded using the composition disclosed herein, which is at least partially cured with a free radical initiator.
[0018] In another aspect, this disclosure provides a method for manufacturing an adhesive article. The method includes combining a composition disclosed herein with a free radical initiator to provide an adhesive composition; applying the adhesive composition to at least one of a first substrate or a second substrate; adhering the first substrate and the second substrate using the adhesive composition; and allowing the adhesive composition to at least partially cure to prepare an adhesive article.
[0019] As used in this article:
[0020] The term "alkyl group" and the prefix "alkane" have only C-C and CH bonds and include straight-chain, branched, and cyclic groups. In some embodiments, unless otherwise specified, the alkyl group has up to 30 carbons (in some embodiments, up to 20, 15, 12, 10, 8, 7, 6, or 5 carbons). The cycloalkyl group can be monocyclic or polycyclic and, in some embodiments, has 3 to 10 cyclic carbon atoms and other alkyl substituents;
[0021] The term "acrylic" refers to acrylic and methacrylic polymers, oligomers, and monomers.
[0022] The term "direct bond to" refers to bonding via a single covalent bond;
[0023] The term "radical polymerization" refers to radical homopolymerization and / or radical copolymerization (i.e., with different monomers / oligomers);
[0024] The term "(meth)acryl" refers to acryl (also known in the art as acryloyl and acrylyl) and / or methacryl (also known in the art as methacryloyl and methacrylyl);
[0025] The term "secondary nitrogen" refers to a neutral nitrogen atom covalently bonded to H and two carbon atoms; and
[0026] The term "tertiary nitrogen" refers to a neutral nitrogen atom covalently bonded to three carbon atoms.
[0027] Terms such as “a,” “an,” “the,” and “the” are not intended to refer to a single entity, but rather to encompass a general category of specific examples that can be used to illustrate the point. The terms “a,” “an,” “the,” and “the” are used interchangeably with the term “at least one (kind).”
[0028] The phrase "including at least one of..." followed by a list means including any item in the list or any combination of two or more items in the list.
[0029] The terms "cured" and "curable" refer to polymer chains linked together by covalent chemical bonds, typically through crosslinking molecules or groups, to form a network polymer. Therefore, in this disclosure, the terms "cured" and "crosslinked" are used interchangeably. Cured or crosslinked polymers are typically characterized by insolubility, but can be swollen in the presence of a suitable solvent.
[0030] Unless otherwise specified, all numerical ranges include their endpoints and the non-integer values between them (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0031] The features and advantages of this disclosure will be further understood upon consideration of the specific embodiments and the appended claims. Detailed Implementation
[0032] A high glass transition temperature is often desirable in adhesives, for example, to allow the adhesive to maintain consistent performance at high temperatures. A common strategy to increase the final glass transition temperature (Tg) of cured epoxy or polyurethane structural adhesives is to apply external heat during the curing process. For example, when 3M's DP420 (a 2-part epoxy adhesive) cures at room temperature for several days, the cured adhesive's Tg only reaches about 44°C, as measured by dynamic mechanical analysis using the methods described in the examples below. If the adhesive is heat-cured at approximately 138°C for several hours, the Tg increases to 80°C. However, low-temperature curing has become increasingly desirable, particularly in applications involving electronic components and plastic bonding, where bonding of heat-sensitive substrates occurs. Low-temperature curing also reduces thermal stress due to CTE (coefficient of thermal expansion) mismatch.
[0033] While known structural adhesives can exhibit good high-temperature performance and durability, the rigid bond they produce after curing can lead to poor impact resistance and subsequent bond failure in the bonded components. Furthermore, adhesives with rigid bonds exhibit high and uneven stress distribution throughout the bond, with stress at the bond edges typically higher than in the middle. This high stress in rigid structural adhesives can cause undesirable deformation of the bonded material (i.e., bond penetration), which can be visually observed, especially when bonding large components such as, for example, automotive panels.
[0034] This disclosure provides compositions that provide adhesives with glass transition temperatures in the range of 120°C to 180°C when cured at room temperature, and adhesive structures that exhibit good adhesion to a variety of substrates even when the substrate has not undergone surface treatment (e.g., corona, flame, abrasion) prior to bonding. In some embodiments, the compositions provide adhesives with available elongation, which improves impact resistance and reduces stress in the adhesive layer. In some embodiments, the compositions of this disclosure provide adhesives with excellent water and moisture resistance.
[0035] The compositions disclosed herein comprise compounds that can be used, for example, as crosslinking agents. The compound comprises at least two X groups and includes a divalent segment L represented by the following formula:
[0036]
[0037] Each bivalent segment L is directly bonded to: (The following is a list of individual covalent bonds shown at each end of the bivalent segment.)
[0038] i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group.
[0039] ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or
[0040] iii) A secondary N atom, which is directly bonded to another divalent chain segment L or X group;
[0041] And a tertiary N atom, which is directly bonded to p another divalent segment L and (2-
[0042] p) X groups, where p is 0, 1 or 2.
[0043] Each R in the bivalent chain segment L 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1 At least some of the groups are -CH2-CH2-CH2-CH2-. In some embodiments, at least 50%, 60%, 70%, 80%, 90%, or 95% of the R groups are present. 1 The radical is -CH2-CH2-CH2-CH2-. Other available R radicals... 1 The groups include -CH2-, -CH2-CH2-, -CH2-CH2-CH2-, –CH(CH3)CH2-, –CH2CH(CH3)-, –CH(CH2CH3)CH2-, –CH2(CH2CH3)CH-, and –CH2(CH3)2C-. In some embodiments, R 1 The groups include -CH2-CH2-CH2-CH2-, and at least one of -CH2-CH2-, -CH2-CH2-CH2-, –CH(CH3)CH2-, or –CH2CH(CH3)-. In some embodiments, all R 1 The group is -CH2-CH2-CH2-CH2-. When all R 1 When the group is -CH2-CH2-CH2-CH2-, the L-divalent segment can be written as
[0044]
[0045] In the binary chain segment L, including any of the embodiments described above for L, each n independently represents a positive integer; for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, 30, 50, 100 or greater. In some embodiments, n may be at most 500 or greater.
[0046] Compounds that can be used as, for example, crosslinking agents comprise at least two X groups. Each X group is independently represented by the following formula:
[0047] CH2=C(R)-C(O)-OVWC(O)-,
[0048] Each R is independently either hydrogen or methyl. In some embodiments, each R is hydrogen. In some embodiments, each R is methyl.
[0049] In the formula CH2=C(R)-C(O)-OVWC(O)-, each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group. In some embodiments, each V is independently an alkylene group optionally inserted with at least one ether bond. In some embodiments, each V is an alkylene group having 2 to 10, 2 to 8, 2 to 6, 2 to 4, 3 to 6, 3 to 8, or 3 to 10 carbon atoms.
[0050] In the formula CH2=C(R)-C(O)-OVWC(O)-, each W is independently O, S, or NR. 2 , where R 2 It is hydrogen or an alkyl group having up to 4 carbon atoms. In some embodiments, each W is independently O or NH. In some embodiments, each W is NH.
[0051] In some embodiments, the compound having at least two X groups and a divalent segment L has a number-average molecular weight of at least 1000 g / mol, 2000 g / mol, 3000 g / mol, 3500 g / mol, or 4000 g / mol and at most 54000 g / mol, 40000 g / mol, 30000 g / mol, or 20000 g / mol, as measured by gel permeation chromatography relative to a polystyrene standard at 40°C according to ASTM Test Method D3016-97 (2018). Specifically, polymers can be analyzed by gel permeation chromatography (GPC) using a Reliant GPC (Waters e2695 pump / autosampler) equipped with a Waters 2424 evaporative light scattering detector and PL-Gel-2 columns; each 300 × 7.5 mm; one 3 μm Mixed-E (nominal MW range up to 30,000 Daltons) and one 5 μm Mixed-D (nominal MW range 200 Daltons to 400,000 Daltons).
[0052] Compounds having at least two X groups and a divalent unit L can be prepared by nucleophilic addition of a primary amine group on a polyamine precursor compound to a reactant compound having carbonate, thiocarbonate, urethane, or isocyanate groups and acrylate or methacrylate groups. An example of a suitable compound of this type is ethyl 2-isocyanate methacrylate (“IEM”). Suitable polyamine precursors have a divalent segment L represented by the following formula:
[0053]
[0054] As described above in any of its embodiments. Each divalent segment L is directly bonded to two N atoms, and each N atom is independently directly bonded to p additional divalent segments L and (2-p) H atoms, where p is 0, 1, or 2. In some embodiments, the polyamine precursor comprises less than 7 wt%, less than 6 wt%, less than 5 wt%, less than 4 wt%, less than 3 wt%, less than 2 wt%, less than 1 wt%, or less than 0.5 wt% of a secondary or tertiary amine group. Suitable polyamine precursors may be obtained under the trade name “DYNAMAR HC-1101” from 3M Company, St. Paul, Minnesota, or prepared, for example, as described in U.S. Patent 3,436,359 (Hubin et al.).
[0055] The compositions disclosed herein may comprise from 2% to 60% by weight or from 5% to 50% by weight of a compound having at least two X groups and a divalent L segment, but this is not required. In some embodiments, the crosslinking agent is present in an amount ranging from 20% to 40% by weight or from 20% to 35% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0056] The compositions disclosed herein comprise an acrylic monomer containing a cycloalkyl group. The cycloalkyl group may have up to 14, 12, or 10 carbon atoms. Such monomers can be used, for example, to increase the Tg of adhesives or sealants made from the compositions. Examples of suitable acrylic monomers containing a cycloalkyl group having up to 14 or 12 carbon atoms include at least one of isobornyl acrylate, isobornyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, tert-butylcyclohexyl acrylate, or tert-butylcyclohexyl methacrylate. In some embodiments, the acrylic monomer containing a cycloalkyl group having up to 14 or 12 carbon atoms comprises at least one of isobornyl acrylate or isobornyl methacrylate. These monomers are available from various commercial sources, such as isobornyl acrylate (SR506 from Sartomer or VISIOMER IBOA from Evonik Performance Materials GmbH), isobornyl methacrylate (SR423A from Sartomer or VISIOMER IBOMA from Evonik Performance Materials GmbH), cyclohexyl methacrylate (VISIOMER c-HMA from Evonik Performance Materials GmbH), dicyclopentyl methacrylate (FANCRYL FA-513M from Hitachi Chemical), isobornylcyclohexyl methacrylate (MM-304 from Designer Molecules, Inc., San Diego, California), and 4-tert-butylcyclohexyl methacrylate (Miramer M1151 from Miwon North America, Exton, Pennsylvania). America,Exton,Pennsylvania)).
[0057] Based on the total weight of the acrylic functional compounds in the composition, an acrylic monomer containing a cycloalkyl group having up to 12 carbon atoms is present in the composition in an amount of at least 15% by weight or 16% by weight. In some embodiments, based on the total weight of the acrylic functional compounds in the composition, an acrylic monomer containing a cycloalkyl group is present in an amount of at least 17%, 18%, 19%, or 20% by weight and up to 40%, 35%, or 30% by weight. In some embodiments, based on the total weight of the acrylic functional compounds in the composition, an acrylic monomer containing a cycloalkyl group is present in an amount ranging from 15% to 35% by weight, 16% to 35% by weight, 17% to 30% by weight, or 17% to 28% by weight.
[0058] The compositions disclosed herein comprise acrylic monomers containing carboxylic acid groups. In some embodiments, the compositions of this disclosure comprise more than 15 wt% or at least 16 wt%, 17 wt%, 18 wt%, 19 wt%, or 20 wt% of an acrylic monomer containing a carboxylic acid group, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomer containing a carboxylic acid group is present in an amount of up to 28 wt%, 30 wt%, or 35 wt%, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomer containing a carboxylic acid group is present in an amount ranging from 15 wt% to 35 wt%, 18 wt% to 35 wt%, 20 wt% to 30 wt%, or 20 wt% to 28 wt%, based on the total weight of the acrylic functional compounds in the composition. Examples of suitable acrylic monomers containing carboxylic acid groups include methacrylic acid, acrylic acid, methacrylic acid, β-acryloyloxyethyl hydrosuccinate, and β-methacryloyloxyethyl hydrosuccinate. Many acrylic monomers containing carboxylic acid groups are commercially available, such as methacrylic acid (VISIOMER GMAA) from Evonik Performance Materials Ltd., and β-methacryloyloxyethyl hydrosuccinate (NK ESTER SA) from Shin-Nakamura Co., Ltd., Arimoto, Japan. In some embodiments, the acrylic monomer containing the carboxylic acid group is methacrylic acid.
[0059] The compositions disclosed herein comprise acrylic monomers containing hydroxyl groups. Acrylic monomers containing hydroxyl groups can be used, for example, to provide compositions with improved adhesion to a variety of plastics (polyamides in some embodiments). In some embodiments, the acrylic monomers containing hydroxyl groups are present in an amount of at least 5% by weight or 10% by weight and up to 25% by weight, 24% by weight, 23% by weight, 22% by weight, 21% by weight, or 20% by weight, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, the acrylic monomers containing hydroxyl groups are present in an amount of at least 5% by weight and up to 25% by weight, at least 10% by weight and up to 24% by weight, or at least 10% by weight and up to 22% by weight, based on the total weight of the acrylic functional compounds in the composition. Selecting the level of the acrylic monomers containing hydroxyl groups in the range of 5% by weight and up to 25% by weight can be used, for example, to provide compositions with improved adhesion to a variety of plastics while maintaining relatively high water and moisture resistance.
[0060] Examples of suitable acrylic monomers containing hydroxyl groups include 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2- and 3-hydroxypropyl acrylate, 2- and 3-hydroxypropyl methacrylate, hydroxybutyl acrylate, hydroxybutyl methacrylate, caprolactone mono(meth)acrylate (available under the trade name "SR-495B" from Sartomer) and other poly(e-caprolactone) mono[2-(meth)acryloyloxyethyl] esters, poly(e-caprolactone) mono[2-acryloyloxyethyl] esters, 2-hydroxy-3-alkoxy methacrylates, 2-hydroxy-3-alkoxy acrylates, and polyethylene glycol monoacrylates and methacrylates. Many acrylic monomers containing hydroxyl groups are commercially available, such as 2-hydroxyethyl methacrylate (available as VISIOMER HEMA 97 and HEMA 98 from Evonik Performance Materials, Inc.), hydroxypropyl methacrylate (available as VISIOMER HPMA 97 and HPMA 98 from Evonik Performance Materials, Inc.), ultra-high purity 2-hydroxyethyl methacrylate (available as VISIOMER UHP HEMA from Evonik Performance Materials, Inc.), polypropylene glycol monomethacrylate (available as MIRAMER M1051 from Amgen North America, Exton, Pennsylvania), and CH2=CHC(O)O(CH2CH2O). 7-9 H (for example, the product name "BLEMMER" may be purchased from Nippon Oil & Fats Company, Tokyo, Japan).
[0061] In some embodiments, the composition comprises methyl methacrylate. Methyl methacrylate is commercially available, including as VISIOMER MMA from Evonik Performance Materials, Inc. In some embodiments, methyl methacrylate is present in amounts of at least 1 wt%, 2 wt%, 3 wt%, 4 wt%, or 5 wt%, and up to 15 wt%, 14 wt%, 13 wt%, 12 wt%, 11 wt%, or 10 wt%, based on the total weight of the acrylic functional compounds in the composition. In some embodiments, methyl methacrylate is present in amounts of at least 1 wt% and up to 10 wt%, at least 2 wt% and up to 10 wt%, or at least 4 wt% and up to 10 wt%, based on the total weight of the acrylic functional compounds in the composition.
[0062] Lauryl methacrylate can be used in some embodiments of the compositions disclosed herein and is available from a variety of commercial sources, such as BASF, Florham Park, New Jersey, as LMA 1214F. However, in some embodiments, the composition is either free of lauryl methacrylate or contains up to 1% lauryl methacrylate based on the total weight of the acrylic functional compounds in the composition.
[0063] In some embodiments, the compositions of this disclosure further comprise acrylic monomers containing phosphate or phosphonate groups. Such monomers can be used, for example, to enhance adhesion to metal substrates. Available acrylic monomers containing phosphate or phosphonate groups include ethylene glycol methacrylate phosphate and phosphonate-functionalized (meth)acrylate monomers (e.g., SIPOMERPAM resins from Solvay Specialty Polymers USA, LLC, or MIRAMER SC1400 and MIRAMER SC1400A from Amgen North America, Exton, Pennsylvania). Vinylphosphonic acid can also be useful. In some embodiments, the compositions of this disclosure further comprise acrylic monomers containing phosphonate groups. Based on the total weight of the acrylic functionalized compounds in the composition, the phosphonate or phosphate-functionalized acrylic monomers may be present in the composition in, for example, up to 10 wt%, 8 wt%, 6 wt%, 5 wt%, or 4 wt%. When present, the phosphonate or phosphate-functionalized acrylic monomers are present in an amount of at least 0.5% by weight, 1% by weight, or 2% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0064] The compositions disclosed herein may also include other monofunctional free radical polymerizable monomers. Examples of usable monomers include 2-phenoxyethyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, alkoxylated lauryl (meth)acrylate, alkoxylated phenolic (meth)acrylate, alkoxylated tetrahydrofurfuryl (meth)acrylate, caprolactone (meth)acrylate, cyclotrimethylolpropane methyl acetal (meth)acrylate, ethylene glycol methyl ether (meth)acrylate, ethoxylated nonylphenol (meth)acrylate, isodecanyl (meth)acrylate, isooctyl (meth)acrylate, octadecyl (meth)acrylate (stearyl (meth)acrylate), tetrahydrofurfuryl (meth)acrylate, tridecyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, and (meth)acrylate. Allyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, isobutyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, n-dodecyl acrylate, 2-methoxyethyl acrylate, 2-ethoxyethyl acrylate, 2-ethoxypropyl acrylate or 3-ethoxypropyl acrylate, 2-(2-ethoxyethoxy)ethyl acrylate, glycidyl acrylate, N-(2-(2-oxo-1-imidazolyl)ethyl)methacrylamide and methacryloylaminoethylvinyl urea (“MAEEU”) purchased from Solvay Specialty Polymers, USA, Inc. as SIPOMER WAM II, and combinations thereof.
[0065] Specific examples of other mono(meth)acrylate monomers that may be used in some embodiments of the compositions disclosed herein include 2-phenoxyethyl methacrylate (available as SR340 from Sartoma), benzyl methacrylate (available as MIRAMER M1183 from Amgen North America, Exton, PA), phenyl methacrylate (available as MIRAMER M1041 from Amgen North America), allyl methacrylate (available as VISIOMER AMA from Evonik Performance, Inc.), n-butyl methacrylate (available as VISIOMER n-BMA from Evonik Performance, Inc.), isobutyl methacrylate (available as VISIOMER i-BMA from Evonik Performance, Inc.), glyceryl methyl acetal methacrylate (available as VISIOMER GLYFOMA from Evonik Performance, Inc.), and 2-(2-butoxyethoxy)ethyl methacrylate (available as VISIOMER...). BDGMA was purchased from Evonik Performance Materials, Inc.; ethyl 2-isocyanate methacrylate (purchased from Showa Denko KK, Tokyo, Japan under the name KarenzMOI); and mono-2-(methacryloyloxy)ethyl phthalate (HEMA phthalate) under product number X-821-2000 was purchased from ESSTECH, Inc., Essington, Pennsylvania.Essington, Pennsylvania), 2-(methacryloyloxy)ethyl maleate (HEMA maleate, purchased from Yishi Technology Co., Ltd. under product number X-846-0000), methoxydiethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-20G), methoxytriethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-30G), methoxytetraethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. under product number M-40G) Chemical Industry Co., Ltd.), methoxytripropylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as M-30PG), butoxydiethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as B-20G), phenoxyethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-1G), phenoxydiethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-2G), dicyclopentadienoxyethyl methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as FANCRYL), methoxytripropylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-2G), dicyclopentadienoxyethyl methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as FANCRYL), methoxytripropylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-2G), dicyclopentadienoxyethyl methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as FANCRYL), methoxytripropylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-1G), phenoxydiethylene glycol methacrylate (purchased from Shin-Nakamura Chemical Industry Co., Ltd. as PHE-2G), dicyclopentadienoxyethyl ... FA-512M was purchased from Hitachi Chemical, Tokyo, Japan; 4-methacryloyloxyethyl trimellitic anhydride (purchased as product A-304 from Design Molecules, Inc.); 2-methacryloyloxyethyl phenylcarbamate (purchased from Polysciences, Inc., Warrington, Pennsylvania); trifluoroethyl methacrylate (purchased from Hampford Research Inc., Stratford, Connecticut); methacrylamide (purchased as VISIOMER MAAmide from Evonik Performance, Inc.); 2-dimethylaminoethyl methacrylate (purchased as VISIOMER MADAME from Evonik Performance, Inc.); 3-dimethylaminopropyl methacrylamide (purchased as VISIOMER DMAPMA from Evonik Performance, Inc.); and combinations thereof.
[0066] The compositions disclosed herein also comprise at least one free radical initiator (i.e., an initiator for free radical polymerization). The free radical initiator can be a single compound or a combination of compounds, referred to as a free radical initiator system.
[0067] In some implementations, the radical initiator is a redox initiator system because single-electron transfer redox reactions can be an efficient method for generating radicals under mild conditions. Redox initiator systems have been described, for example, in Progress in Polymer Science (1999), Vol. 24, pp. 1149–1204.
[0068] In some embodiments, the redox initiator system is a blend of a peroxide and an amine, wherein polymerization is initiated by the decomposition of the organic peroxide, which is activated by a redox reaction with an amine reducing agent. Typically, the peroxide is benzoyl peroxide, and the amine is a tertiary amine. Aromatic tertiary amines are suitable for generating primary groups, among which N,N-dimethyl-4-toluidine (“DMT”) is the most common amine reducing agent.
[0069] In some embodiments, the redox curing initiator system comprises a barbituric acid derivative and a metal salt. In some embodiments, the barbituric acid / metal salt curing initiator system may also comprise an organic peroxide, an ammonium chloride salt (e.g., benzyltributylammonium chloride), or a mixture thereof.
[0070] Examples of free radical initiators based on barbituric acid include redox initiator systems having (i) a barbituric acid derivative and / or malonyl sulfonamide and (ii) an organic peroxide selected from monofunctional or polyfunctional carboxylic acid peroxide esters. Examples of available barbituric acid derivatives include 1,3,5-trimethylbarbituric acid, 1,3,5-triethylbarbituric acid, 1,3-dimethyl-5-ethylbarbituric acid, 1,5-dimethylbarbituric acid, 1-methyl-5-ethylbarbituric acid, 1-methyl-5-propylbarbituric acid, 5-ethylbarbituric acid, 5-propylbarbituric acid, 5-butylbarbituric acid, 1-benzyl-5-phenylbarbituric acid, 1-cyclohexyl-5-ethylbarbituric acid, and thiobarbituric acid, as mentioned in the published German patent application DE 42 19 700 A1 (Imai et al.).
[0071] Barbiturates and barbiturates described in U.S. Patents 3,347,954 (Bredereck et al.) and 9,957,408 (Thompson), as well as malonyl sulfonamides disclosed in European Patent No. EP 0 059 451 B1 (Schmitt et al.), may also be used in embodiments of this disclosure. Examples of malonyl sulfonamides include 2,6-dimethyl-4-isobutylmalonyl sulfonamide, 2,6-diisobutyl-4-propylmalonyl sulfonamide, 2,6-dibutyl-4-propylmalonyl sulfonamide, 2,6-dimethyl-4-ethylmalonyl sulfonamide, or 2,6-dioctyl-4-isobutylmalonyl sulfonamide.
[0072] Barbiturate-based radical initiators typically comprise monofunctional or polyfunctional carboxylic acid peroxides as organic peroxides. Within the meaning of this disclosure, carbonate peroxides are also included in the category of polyfunctional carboxylic acid peroxides. Suitable examples include diisopropyl carbonate-peroxide diester, neodecanoic acid-tert-butyl-peroxide, neodecanoic acid-tert-amyl-peroxide, maleic acid-tert-butyl-monoperoxide, benzoic acid-tert-butyl-peroxide, 2-ethylhexanoic acid-tert-butyl-peroxide, 2-ethylhexanoic acid-tert-amyl-peroxide, monoisopropyl carbonate-monotert-butyl-peroxide, dicyclohexyl carbonate-peroxide, dimyristyl carbonate-peroxide, and carbonate... Diceryl peroxide, di(2-ethylhexyl)-peroxide, tert-butyl-peroxy-(2-ethylhexyl)-peroxide or 3,5,5-trimethylhexanoic acid-tert-butyl-peroxide, benzoic acid-tert-pentyl-peroxide, acetic acid-tert-butyl-peroxide, di(4-tert-butyl-cyclohexyl)-peroxide, neodecanoic acid-isopropylbenzene-peroxide, neopentanoic acid-tert-pentyl-peroxide and neopentanoic acid-tert-butyl-peroxide.
[0073] Specifically, in some embodiments of this disclosure, tert-butyl-peroxy-(2-ethylhexyl) carbonate (available from Arkema, Inc., King of Prussia, PA, via LUPEROX TBEC) or tert-butyl-peroxide 3,5,5-trimethyl-hexanoate (available from Arkema, via LUPEROX 270) can be used as organic peroxides.
[0074] Metal salts that can be used with barbituric acid derivatives may include transition metal complexes, particularly salts of cobalt, manganese, copper, and iron. When the metal salt is a copper compound, it may have the general formula CuXn, where X is an organic and / or inorganic anion, and n = 1 or 2. Examples of suitable copper salts include copper chloride, copper acetate, copper acetylacetonate, copper naphthenate, copper salicylate, or complexes of copper with thiourea or ethylenediaminetetraacetic acid, and mixtures thereof. In some embodiments, the copper salt is copper naphthenate.
[0075] Another redox initiator system applicable to embodiments of this disclosure comprises an inorganic peroxide, an amine-based reducing agent, and a promoter, wherein the amine may be an aromatic and / or aliphatic amine, and the polymerization promoter is at least one selected from the group consisting of sodium benzenesulfinate, sodium p-toluenesulfinate, sodium 2,4,6-triisopropylbenzenesulfinate, sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sodium bisulfate, and potassium bisulfate. Examples of inorganic peroxides that can be used in this system are persulfates, as described in U.S. Patent 8,545,225 (Takei et al.).
[0076] In some embodiments, the compositions of this disclosure comprise a free radical initiator comprising a metal salt (e.g., copper naphthenate) and an ammonium salt (e.g., benzyltributylammonium chloride). In some embodiments, the compositions comprise a curing initiator system comprising a barbituric acid derivative and a metal salt, and optionally comprising at least one of an organic peroxide and an ammonium chloride salt.
[0077] The composition may include at least one photoinitiator, alone or in combination with other free radical initiators, which is activated by light (typically ultraviolet (UV) lamps), but other light sources such as LED lamps, xenon flash lamps and lasers may also be used if the photoinitiator is appropriately selected.
[0078] Available photoinitiators include those known to be usable for photocuring free radical polyfunctional (meth)acrylates. Examples of suitable photoinitiators include benzoin and its derivatives such as α-methylbenzoin; α-phenylbenzoin; α-allylbenzoin; α-benzyl benzoin; benzoin ethers such as benzoyl dimethyl ketal (e.g., available as OMNIRAD BDK from IGM Resins USA Inc., St. Charles, Illinois), benzoin methyl ether, benzoin ethyl ether, benzoin n-butyl ether; acetophenone and its derivatives such as 2-hydroxy-2-methyl-1-phenyl-1-propanone (e.g., available as OMNIRAD 1173 from IGM Resins USA Inc.) and 1-hydroxycyclohexylphenyl ketone (e.g., available as OMNIRAD 184 from IGM Resins USA Inc.); 2-methyl-1-[4-(methylthio)phenyl]-2-(4-morpholino)-1-propanone (e.g., available as OMNIRAD BDK from IGM Resins USA Inc.) 907 (purchased from IGM Resins, USA); 2-benzyl-2-(dimethylamino)-1-[4-(4-morpholino)phenyl]-1-butanone (e.g., purchased from IGM Resins, USA as OMNIRAD 369); and triarylphosphine and phosphine oxide derivatives, such as ethyl 2,4,6-trimethylbenzoylphenylphosphonate (e.g., purchased from IGM Resins, USA as TPO-L) and bis-(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (e.g., purchased from IGM Resins, USA as OMNIRAD 819).
[0079] Other examples of available photoinitiators include pivaloin ether, anethole ether, anthraquinones (e.g., anthraquinone, 2-ethylanthraquinone, 1-chloroanthraquinone, 1,4-dimethylanthraquinone, 1-methoxyanthraquinone, or benzoanthraquinone), halomethyltriazines, benzophenone and its derivatives, iodonium and sulfonium salts, titanium complexes such as bis(n5-2,4-cyclopentadien-1-yl)-bis[2,6-difluoro-3-(1H-pyrrolo-1-yl)phenyl]titanium (e.g., available under the trade name CGI 784DC from BASF, Florem Park, NJ); halomethyl-nitrobenzene (e.g., 4-bromomethylnitrobenzene), and combinations of photoinitiators in which one component is monoacylphosphine oxide or diacylphosphine oxide (e.g., available under the trade names IRGACURE 1700, IRGACURE 1800, and IRGACURE). Purchased in 1850 from BASF, Florem Park, New Jersey, and in OMNIRAD 4265 from IGM Resins USA.
[0080] Free radical initiators can also be thermally activated free radical initiators, such as azo initiators (e.g., azobisisobutyronitrile) or peroxides (e.g., benzoyl peroxide).
[0081] The free radical initiator can be used in the composition in an amount sufficient to allow the curable composition to have a adequate rate of curing free radical reaction when polymerization is initiated; these amounts can be readily determined by those skilled in the art. In some embodiments of this disclosure, the free radical initiator is present in the curable composition at a level of 0.1% to 10% by weight, or 0.5% to 5% by weight, of the free radical polymerizable component in the composition; however, this is not required.
[0082] In some embodiments, the compositions disclosed herein comprise, based on the total weight of the acrylic functional compounds in the composition, 20% to 30% by weight of an acrylic monomer containing a carboxylic acid group, 10% to 20% by weight of an acrylic monomer containing a hydroxyl group, 16% to 30% by weight of an acrylic monomer containing a cycloalkyl group, 0.5% to 10% by weight of an acrylic monomer containing a phosphonate group, 4% to 10% by weight of methyl methacrylate, and 15% to 30% by weight of a compound containing a divalent segment L and at least two X groups, and based on the weight of the curable composition, 0.1% to 10% by weight of at least one free radical initiator. In some embodiments, based on the total weight of the acrylic functional compounds in the composition, the compositions of this disclosure comprise 15% to 25% by weight of an acrylic monomer containing a carboxylic acid group, 15% to 25% by weight of an acrylic monomer containing a hydroxyl group, 15% to 25% by weight of an acrylic monomer containing a cycloalkyl group, 4% to 10% by weight of methyl methacrylate, 0.5% to 10% by weight of an acrylic monomer containing a phosphonate ester group, and 20% to 35% by weight of a compound containing a divalent segment L and at least two X groups. In some of these embodiments, the composition comprises 0.1% to 10% by weight of at least one free radical initiator based on the total weight of the curable composition.
[0083] The compositions disclosed herein may include other components that can be used in, for example, sealant and adhesive compositions. For example, the compositions may contain at least one of the following: toughening agents (e.g., acrylic core / shell polymers; styrene-butadiene / methacrylate core / shell polymers; acrylonitrile-butadiene rubber), plasticizers (e.g., aliphatic and aromatic hydrocarbons, alkyl esters, alkyl ethers, aryl esters and aryl ethers), tackifiers, corrosion inhibitors, UV stabilizers, antioxidants, free radical inhibitors, flame retardants, thixotropic agents such as pyrolytic silica, dyes, pigments (e.g., iron oxide, brick dust, carbon black and titanium dioxide), reinforcing agents (e.g., silica, magnesium sulfate, calcium sulfate and beryllium aluminum silicate), clays such as bentonite, other suitable fillers (e.g., glass beads, talc and calcium metasilicate), dispersants, wetting agents, adhesion promoters (e.g., silane coupling agents), antistatic agents, thermally and / or electrically conductive particles, foaming agents and hollow polymers or ceramic microspheres (e.g., glass bubbles). In some embodiments, the compositions disclosed herein contain fillers. Further examples of fillers that can be used in some embodiments of the compositions disclosed herein include at least one of the following: microfibrillated polyethylene, pyrolytic silica, talc, wollastonite, aluminosilicate clay (e.g., hydrous kaolin), phlogopite, calcium carbonate, kaolin, metal oxides (e.g., barium oxide, calcium oxide, magnesium oxide, zirconium oxide, titanium oxide, zinc oxide), and nanoparticle fillers (e.g., nano-silica, nano-zirconia).
[0084] The compositions disclosed herein may be provided as a single-component or two-component composition, depending, for example, on the chosen radical initiator. When using a radical initiator system comprising a combination of components, some of the components may be included in a first portion of the two-component composition, while others may be included in a second portion of the two-component composition. In some embodiments, if the composition disclosed herein is the first portion of a two-component composition, the first portion may include at least one of a metal salt or ammonium chloride salt as described above in any of their embodiments, and the second portion may include at least one of a barbituric acid derivative and an organic peroxide. The second portion may be, for example, in the form of a paste, comprising at least one of a plasticizer or other diluent and optionally a toughening agent, dye, pigment, tackifier, or filler, as described above. For example, some peroxide pastes are commercially available. An example of a usable second portion is an acrylic adhesive accelerator from 3M Company, St. Paul, Minnesota, under the trade name “3MSCOTCH-WELD DP8410NS”.
[0085] In some embodiments, if the composition of this disclosure is the first part of a two-part composition, the first and second parts can be combined in any suitable volume ratio. For example, the first and second parts can be combined in a volume ratio ranging from about 5:100 to about 100:1, from about 10:100 to about 50:1, or from about 1:1 to 20:1.
[0086] The first and second portions can be located in any suitable system or kit for containing, mixing, and dispensing the first and second portions. This system can be suitable for large-scale industrial applications or small-scale applications. Any system may include a first chamber and a second chamber for storing the respective first and second portions. The dimensions of the chambers may be set to suit any application and formed of plastic, metal, or any other suitable material. A dispenser may be adapted to receive the first and second portions and dispense the mixture of the first and second portions onto a substrate. The dispenser may be used to facilitate mixing of the first and second portions, or a mixing chamber may be located upstream of the dispenser and in fluid communication with the first and second chambers. The mixing chamber may be adapted to rotate to facilitate mixing, or the mixing chamber may include multiple baffles to induce rotation of the first and second portions.
[0087] To facilitate movement of the first and second portions, the system may include elements such as one or more plungers or one or more pumps. One or more plungers may be used in a handheld system. In these embodiments, a user may push one or both plungers between at least a first position and a second position to force the first and second portions through the system. If one plunger is present, the first and second portions can be dispensed in equal volumes or a predetermined volume ratio.
[0088] Pumps can be used in industrial applications where a large or continuous supply of a first and a second portion is dispensed. These systems may include one or more pumps in fluid communication with the first and second chambers. The one or more pumps may be located downstream of the first and second chambers, but upstream of the mixing chamber. In embodiments of a system in which two pumps are in fluid communication with the respective first and second chambers, the pumps may be adapted or controlled to pump equal volumes of the first and second portions, or to pump different amounts of the portions according to a predetermined volume ratio.
[0089] The compositions disclosed herein can be at least partially cured by exposure to photochemical electromagnetic radiation (e.g., ultraviolet and / or visible light), thermal energy (e.g., in an oven, infrared radiation, or thermal conduction), by exposure to oxygen, by combining two portions of a two-part composition, or any combination thereof.
[0090] After at least partial curing, a crosslinked composition is typically obtained, and if fully cured, it can be suitable as a structural adhesive for bonding two adherends. In such applications, the composition is typically sandwiched between the adherends and cured at least partially; for example, sufficient to achieve at least the desired level of bond strength.
[0091] The compositions disclosed herein can be used, for example, to bond a first substrate to a second substrate to provide an bonded article. Many types of substrates can be bonded to the compositions disclosed herein, such as metals (e.g., stainless steel or aluminum), glass (e.g., which may be coated with indium tin oxide), polymers (e.g., plastics, rubber, thermoplastic elastomers, or thermosetting materials), or composite materials. Composite materials can be made from any two or more constituent materials with different physical or chemical properties. When components are combined to prepare composite materials, materials with properties different from those of the individual components are typically obtained. Some examples of useful composite materials include fiber-reinforced polymers (e.g., carbon fiber-reinforced epoxy resins and glass-reinforced plastics); metal matrix compositions; and ceramic matrix composites. Available polymer substrates for bonding include polymers such as polyolefins (polypropylene, polyethylene, high-density polyethylene, polypropylene blends), polyamide 6 (PA6), polyamide 6,6, acrylonitrile butadiene styrene (ABS), polycarbonate (PC), PC / ABS blends, polyvinyl chloride (PVC), polyamide (PA), polyurethane (PUR), thermoplastic elastomers (TPE), polyoxymethylene (POM), polystyrene, poly(meth)methyl acrylate (PMMA), polyvinyl chloride (PVC), polyetheretherketone (PEEK), and combinations thereof. The substrate may also include a metallic coating on such polymers. The compositions disclosed herein can be used, for example, to bond electronic products as well as automotive and aerospace components.
[0092] In some embodiments, a first substrate can be bonded to a second substrate by: combining the composition with an accelerator to provide an adhesive composition; applying the composition of this disclosure to at least a portion of a surface of the first substrate; adhering the first and second substrates using the adhesive composition; and allowing the adhesive composition to cure to prepare an bonded article. While it is impractical to list specific curing temperatures applicable to all cases, generally suitable temperatures are in the range of about 23°C to about 200°C. In some embodiments, advantageously, the composition can be cured at room temperature (e.g., 23°C to 30°C) for, for example, at least 60 minutes, 90 minutes, 120 minutes, 6 hours, 12 hours, 24 hours, 48 hours, or 72 hours.
[0093] As shown in the following examples, the compositions of this disclosure can be cured at room temperature to provide an adhesive with a glass transition temperature of 138°C to 158°C. In some embodiments, the adhesive has an elongation of 51%, which allows it to be used for bonding substrates at low temperatures. The adhesive can bond a variety of materials, including polyamides, for which it has an overlap shear strength of 1000 psi at room temperature. In another embodiment, the adhesive bonds to aluminum and has a significant overlap shear strength of at least 1000 psi at 120°C. As shown in Tables 10 and 11, the adhesive bonding is resistant to water or high humidity.
[0094] Some implementation schemes disclosed herein
[0095] In a first embodiment, this disclosure provides a composition comprising:
[0096] Based on the total weight of the acrylic functional compounds in the composition, at least 16% by weight of an acrylic monomer comprising a cycloalkyl group having up to 12 carbon atoms;
[0097] Acrylic monomers containing carboxylic acid groups;
[0098] Acrylic monomers containing hydroxyl groups; and
[0099] A compound comprising a divalent segment L and at least two X groups, wherein the divalent segment L is represented by the following formula:
[0100]
[0101] Each of the two-valent segments L is directly bonded to:
[0102] i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group.
[0103] ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or
[0104] iii) A secondary N atom, which is directly bonded to another divalent chain segment L or X group;
[0105] And a tertiary N atom, which is directly bonded to p another divalent segment L and (2-
[0106] p) X groups, where p is 0, 1, or 2.
[0107] Each R 1 Independently represents an alkylene group having 1 to 4 carbon atoms, provided that R 1At least some of the groups are -CH2-CH2-CH2-CH2-, where each n independently represents a positive integer.
[0108] The number, and each X group is independently represented by the following formula:
[0109] CH2=C(R)-C(O)-OVWC(O)-
[0110] Each W is independently O, S, or NR. 2 , where R 2 It is hydrogen or an alkyl group having up to 4 carbon atoms, and wherein each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group.
[0111] In a second embodiment, this disclosure provides a composition according to the first embodiment, wherein at least 50% R 1 The group is -CH2-CH2-CH2-CH2-.
[0112] In a third embodiment, this disclosure provides a composition according to the first or second embodiment, wherein the divalent L-segment is represented by the following formula:
[0113]
[0114] Each n represents a positive integer.
[0115] In a fourth embodiment, this disclosure provides a composition according to any one of the first to third embodiments, wherein an acrylic monomer containing a hydroxyl group is present in an amount of at least 5% by weight or 10% by weight and at most 25% by weight, 24% by weight, 23% by weight, 22% by weight, 21% by weight or 20% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0116] In a fifth embodiment, this disclosure provides a composition according to any one of the first to fourth embodiments, the composition further comprising methyl methacrylate.
[0117] In a sixth embodiment, this disclosure provides a composition according to any one of the first to fifth embodiments, the composition further comprising methyl methacrylate in an amount of at least 4% and at most 10% by weight based on the total weight of the acrylic functional compounds in the composition.
[0118] In a seventh embodiment, this disclosure provides a composition according to any one of the first to sixth embodiments, wherein an acrylic monomer comprising a carboxylic acid group is present in an amount of at least 15% or 20% by weight and at most 35% or 30% by weight, based on the total weight of the acrylic functional compounds in the composition.
[0119] In the eighth embodiment, this disclosure provides a composition according to any one of the first to seventh embodiments, wherein the composition is free of lauryl methacrylate or contains up to 1% lauryl methacrylate based on the total weight of the acrylic functional compounds in the composition.
[0120] In a ninth embodiment, this disclosure provides a composition according to any one of the first to eighth embodiments, comprising an acrylic monomer having a cycloalkyl group having up to 12 carbon atoms, including at least one of isobornyl acrylate, isobornyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, tert-butylcyclohexyl acrylate, or tert-butylcyclohexyl methacrylate.
[0121] In a tenth embodiment, this disclosure provides a composition according to any one of the first to ninth embodiments, comprising an acrylic monomer having a cycloalkyl group having up to 12 carbon atoms, including at least one of isobornyl acrylate or isobornyl methacrylate.
[0122] In the eleventh embodiment, this disclosure provides a composition according to any one of the first to tenth embodiments, wherein an acrylic monomer comprising a cycloalkyl group is present in an amount of at least 17 wt%, 18 wt%, 19 wt%, or 20 wt%, and at most 40 wt%, 35 wt%, or 30 wt%, based on the total weight of the acrylic functional compound in the composition.
[0123] In the twelfth embodiment, this disclosure provides a composition according to any one of the first to eleventh embodiments, wherein the compound comprising a divalent segment L and at least two X groups is present in an amount ranging from 20% by weight to 40% by weight or 35% by weight, based on the total weight of the acrylic functional compound in the composition.
[0124] In the thirteenth embodiment, this disclosure provides a composition according to any one of the first to twelfth embodiments, the composition further comprising a toughening agent.
[0125] In the fourteenth embodiment, this disclosure provides a composition according to any one of the first to thirteenth embodiments, the composition further comprising a filler.
[0126] In the fifteenth embodiment, this disclosure provides a composition according to any one of the first to fourteenth embodiments, the composition further comprising a free radical initiator.
[0127] In a sixteenth embodiment, this disclosure provides a composition according to any one of the first to fifteenth embodiments, the composition further comprising a free radical initiator.
[0128] In the seventeenth embodiment, this disclosure provides a composition according to any one of the first to sixteenth embodiments, the composition being packaged as a first part of a two-part adhesive composition, wherein the second part comprises a free radical initiator.
[0129] In an eighteenth embodiment, this disclosure provides an adhesive comprising a composition according to any one of the first to fifteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the adhesive composition has a glass transition temperature in the range of 120°C to 180°C.
[0130] In a nineteenth embodiment, this disclosure provides an adhesive comprising a composition according to any one of the first to fifteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the adhesive bonds to a polyamide and has an overlap shear strength of at least 1000 psi at room temperature.
[0131] In a twentieth embodiment, this disclosure provides an adhesive comprising a composition according to any one of the first to fifteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the adhesive bonds to aluminum and has an overlap shear strength of at least 1000 psi at 120°C.
[0132] In a twenty-first embodiment, the present disclosure provides an article of manufacture that is bonded using a composition according to any one of the first to fifteenth embodiments, the composition being at least partially cured with a free radical initiator, wherein the article comprises at least one of a polyamide, a metal, or an epoxy resin composite material.
[0133] In a twenty-second embodiment, this disclosure provides a method for preparing an adhesive article comprising a first substrate and a second substrate, the method comprising:
[0134] The composition according to any one of the first to fourteenth embodiments is combined with a free radical initiator to provide an adhesive composition;
[0135] The adhesive composition is applied to at least one of a first substrate or a second substrate;
[0136] The adhesive composition is used to adhere the first substrate and the second substrate; and
[0137] The adhesive composition is allowed to cure at least partially in order to prepare an adhesive article.
[0138] In the twenty-third embodiment, this disclosure provides a method according to the twenty-second embodiment, wherein at least one of the first substrate or the second substrate comprises at least one of nylon, acrylonitrile butadiene styrene (poly(meth)methacrylate) or polyvinyl chloride.
[0139] The purposes and advantages of this disclosure are further illustrated by the following non-limiting embodiments, but the specific materials and quantities referenced in these embodiments, as well as other conditions and details, should not be construed as undue limitation of this disclosure.
[0140] Example
[0141] Unless otherwise specified, all parts, percentages, proportions, etc., used in the examples and other parts of the specification are by weight, and all reagents used in the examples are derived from or available from general chemical suppliers, such as Sigma-Aldrich, St. Louis, MO, USA, or can be synthesized by conventional methods. The following abbreviations are used in this section: in = inch, g = gram, min = minute, ℃ = degree Celsius, ℉ = degree Fahrenheit, RH = relative humidity, Hz = hertz, J = joule, ° = degree angle, μm = micrometer, and rpm = revolutions per minute.
[0142] Table 1: Materials used in the examples
[0143]
[0144]
[0145] Test methods
[0146] Tensile test of cured film
[0147] A cured film of the composition was prepared by extruding the two-part composition of Example 1 or 2, or Exemplary Example A or B, onto a silicone polyester liner via a static mixer. Using a second silicone polyester liner, an adhesive film was prepared between the two liners to a thickness of approximately 1 mm (0.04 in) using a simple doctor blade coater. The adhesive film was allowed to cure at room temperature for at least 24 hours prior to testing. Tensile elongation was measured according to ASTM Standard D638–14, 2015, “Standard Test Method for Tensile Properties of Plastics,” using a TYPE-V die for sample cutting and a clamp test speed of 50.8 mm (2 in) / min.
[0148] Dynamic mechanical analysis (DMA)
[0149] Membrane samples were prepared using the membrane prepared for tensile testing as described above. The membrane samples were cut into approximately 5-6 mm wide × 1 mm thick × 57 mm long pieces (0.20 in-0.24 in × 0.04 in × 2.25 in) and tested using a double cantilever clamp on a DMAQ800 (TA Instruments Inc., New Castle, DE) with the following settings: frequency = 1 Hz, oscillation amplitude = 15 μm, and minimum oscillation force = 0.02 N. The membrane samples were equilibrated to -50°C (122°F) and held at this temperature for five minutes, then gradually increased to 200°C (392°F) at a rate of 3.0°C (37.4°F) / minute.
[0150] Overlap shear test
[0151] Overlap shear test specimens were prepared on nylon 6,6 and aluminum substrates using the resulting mixed adhesive. Nylon 6,6 specimens, obtained from Plastics International, Eden Prairie, MN, measured 6.35 × 25.4 × 101.6 mm (1 / 4 × 1 × 4 in) and were wiped with isopropyl alcohol only prior to bonding. BlastedGreen FR4 glass epoxy specimens (obtained from Plastics International, measured 2.54 × 10.16 × 0.318 cm (1 in × 4 in × 0.125 in)) were wiped with isopropyl alcohol only prior to bonding. The aluminum specimens, obtained from Joseph T. Ryerson and Son, Inc., Coon Rapids, MN, measured 2.54 × 10.16 × 0.16 cm (1 in × 4 in × 1 / 16 in) and were wiped with isopropanol before bonding. A 1.27 cm (1 / 2 in) overlap was used when preparing the overlap shear specimens. The adhesive layer was clamped with a long-tail clip during curing and removed after 24 hours at 25°C. Overlap shear tests were performed on the aluminum specimens at a 5,620 lb (25 kN) force sensor, while those on the nylon 6,6 specimens were performed on a 2,250 lb (10 kN) force sensor. The nylon 6,6 overlap shear test was run at 50.8 mm (2 in) / min, and the aluminum overlap shear test was run at 2.54 mm (0.1 in) / min. Report the peak stress value (psi), and each value is the average of three samples.
[0152] Water immersion overlapping shear test
[0153] Nine overlapping shear samples were prepared using sandblasted FR4 glass epoxy resin specimens (obtained from Plastics International, measured 2.54 × 10.16 × 0.318 cm (1 in × 4 in × 0.125 in)). The OLS samples were bonded with a 1.27 cm (0.5 in) overlap and the adhesive was allowed to cure for at least 24 hours. Three of the nine samples served as controls and were stored in the laboratory under ambient conditions. The remaining six OLS samples were placed in 1-gallon wide-mouth glass flasks, and the flasks were filled with water to completely submerge the samples. The flasks were placed in an oven set to 60°C (140°F). After one week, three samples were removed from the flasks and allowed to equilibrate to room temperature for approximately one hour. The OLS (peak stress) of the three exposed samples and the three control samples was then tested, and the % strength retention was reported. After two weeks, the OLS (peak stress) of the remaining three exposed samples was tested and compared with the controls. The % strength retention was reported. Note that in some cases, only six OLS samples were tested (three control samples and three two-week exposed samples). The results of the test are reported in Table 10.
[0154] Mud application test
[0155] Ten overlapping shear samples were prepared using abraded aluminum specimens, sourced from Joseph T. Ryerson and Son, Coon Lapis, Minnesota, measuring 2.54 × 10.16 × 0.16 cm (1 in × 4 in × 1 / 16 in). The specimens were ground using a mat labeled “SCOTCH BRITE” (3M, St. Paul, Minnesota) and mounted on an electric palm sander, subsequently wiped with MEK solvent before bonding. The OLS samples were bonded with a 1.27 cm (0.5 in) overlap and the adhesive was allowed to cure for at least 24 hours. Five of the ten samples served as controls and were stored in the laboratory under ambient conditions. The remaining five OLS samples were carefully wrapped in 100% cotton wadding. The packaged samples were placed in a bag bearing the trade name "ZIPLOC" (SC Johnson and Son, Inc., Racine, WI), and distilled water was added in an amount ten times the total weight of the cotton wadding used. This bag was then sealed and placed in a second, identically sealed bag. The double-bag sample was then placed on an aluminum tray and placed in an oven set to 71°C (160°F) for two weeks. After two weeks in the 71°C (160°F) oven, the sample was immediately placed in a freezer at -17.8°C (0°F) for two hours. After two hours in the freezer, the sample was thawed for two hours and then immediately subjected to a standard overlapping shear test at 2.54 mm (0.1 in) / min. The OLS of both the mud-coating sample and the control sample were tested simultaneously, and the % strength retention was again reported based on the average of all controls. The results of this test are reported in Table 11.
[0156] Bell peel strength test
[0157] Follow the procedure outlined in ASTM D3167. Apply adhesive to an etched aluminum substrate (1.0" wide × 0.063" thick × 8.0" long), adding 17 mil spacer beads to the applied adhesive before bonding. Then apply a second aluminum substrate (1.0" wide × 0.020" thick × 10" long) to the adhesive and compress the bonded aluminum test specimen using a metal plate of approximately 10 lb. Allow the adhesive to cure for at least three days. After curing, perform a peel test using a 200 lb force sensor and a floating roller device. Pull the specimen at 6' / min.
[0158] Preparation of methacryloyloxyurea-terminated branched diamine poly(tetrahydrofuran) (EPX-IEM)
[0159] DYNAMAR HC-1101 (“HC-1101”) was heated at 65°C to melt the solid material and reduce its viscosity. Molten HC-1101 (245.0 g) was loaded into a three-necked round-bottom flask equipped with a distillation head, thermocouple, and top-mounted stirrer. The flask was purged with nitrogen and heated to 70°C. Methyl ethyl ketone (60 mL) was added to the highly viscous heated “HC-1101” with stirring. The same amount of methyl ethyl ketone was then distilled off under vacuum to obtain dried “HC-1101”. 5.32 g of IEM was added dropwise to the dried “HC-1101” under nitrogen, and stirring was continued at 70°C for 16 hours. Isocyanate consumption was monitored by transmission-FTIR spectroscopy. The resulting material was discharged at 70°C to provide 196.2 g (78% yield) of a viscous, pale yellow oil, which solidified upon cooling to ambient temperature.
[0160] Example 1
[0161] The NTR03-42-580 adhesive resin mixture was prepared by combining the components shown in Table 3 in a polypropylene MAX 600 DAC cup (FlackTek, Inc., Landrum, SC, South Carolina). Each component in each group of materials was rapidly mixed as described. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, isobornyl methacrylate (IBOMA), benzyl tributylammonium chloride (N+CL-), and methoxyethyl hydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2VAC (FlackTek, Inc., Landrum, SC, 29356, South Carolina). Then, the solid EPX-IEM material was melted in an oven at 71°C (160°F) for several hours, and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then add XT100 to the rapid mixer cup and rapidly mix the mixture at 2250 rpm for 4 minutes. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 2250 rpm for 4 minutes. Next, add PW80, SB, and SL300 and rapidly mix the mixture at 2250 rpm for 4 minutes. After mixing, cool the material in a freezer for approximately 5 minutes. Then add methyl methacrylate and rapidly mix at 2000 rpm for 1 minute. After rapid mixing, degas the final binder resin mixture by covering the mixing cup with a polypropylene cap containing a vent, and then mix at a reduced pressure of 0.68 psi (approximately 35 torr) at 1500 rpm for 2 minutes. The prepared adhesive resin mixture was individually loaded into 10 sections of a 10:1 dual-syringe dispenser, with an accelerator of the commercially available acrylic adhesive "3M SCOTCH-WELDDP8810NS" (3M Corporation, St. Paul, Minnesota) used in one section of the dispenser in each case. All adhesives for the overlap shear test were prepared by dispensing approximately 0.3 grams of the adhesive resin mixture and accelerator resin via a static mixing tip.
[0162] Table 3: Components of Example 1
[0163] IBOMA 18.61 HEMA 13.00 methacrylic acid 19.33 MMA 6.00 CLEARSTRENGTH XT100 5.04 MEHQ 0.05 N+Cl- 0.77 EPX-IEM 18.00 CuNap 0.11 PAM 200 3.32 ESS50F 0.68 HDK H18 2.04 PW80 12.51 CB 0.17 SL300 0.37 total 100.00
[0164] Example 2
[0165] Example 2 was prepared by combining the components shown in Table 4 in a polypropylene MAX 600 DAC cup (Sonchon Corporation, Landrum, South Carolina). Each of the material components in each group was rapidly mixed as described. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, isobornyl methacrylate (IBOMA), benzyl tributylammonium chloride (N+CL-), and methoxyethyl hydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2VAC (Sonchon Corporation, Landrum, South Carolina). Then, the solid EPX-IEM material was melted in an oven at 71°C (160℉) for several hours, and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 2250 rpm for 4 minutes. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 2250 rpm for 4 minutes. Then add PW80, SB, and SL300 and rapidly mix the mixture at 2250 rpm for 4 minutes. After mixing, cool the material in a freezer for approximately 5 minutes. Then add methyl methacrylate, followed by rapid mixing at 2250 rpm for 1 minute. After rapid mixing, allow the adhesive mixture to cool. Then degas the final adhesive resin mixture by covering the mixing cup with a polypropylene cap containing vent holes and mixing at a high shear rate of 1500 rpm for 2 minutes under reduced pressure of 0.68 psi (approximately 35 Torr). The prepared adhesive resin mixtures were individually loaded into 10 sections of a 10:1 dual-syringe dispenser, using an accelerator of the trade name "3M SCOTCH-WELD DP8810NS" acrylic adhesive (3M Company, St. Paul, Minnesota) in 1 section of the dispenser in each case. All adhesives for the overlap shear test were prepared by dispensing approximately 0.3 grams of the adhesive resin mixture and accelerator resin via a static mixing tip.
[0166] Table 4: Components of Example 2
[0167] IBOMA 13.95 HEMA 16.00 methacrylic acid 16.00 MMA 5.00 CLEARSTRENGTH XT100 6.33 MEHQ 0.05 N+Cl- 0.57 EPX-IEM 24.00 CuNap 0.11 PAM 200 3.35 ESS50F 0.67 HDK H18 2.51 PW80 8.94 CB 0.15 SL300 0.34 total 100.00
[0168] Exemplary Example A
[0169] Exemplary Example A was prepared by combining the components shown in Table 5 in a polypropylene MAX 600DAC cup (Sonchong Corporation). Each of the material components in each group was rapidly mixed at 1750 rpm for 4 minutes, unless otherwise specified. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, benzyltributylammonium chloride (N+CL-), and methoxyethylhydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2VAC (Sonchong Corporation). Then, the solid EPX-IEM material was melted in an oven at 66°C (150℉), and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Next, the Baymod rubber material was added, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. The material was allowed to cool for 5 minutes, and then rapidly mixed at 1900 rpm for 4 minutes. Then repeat the rapid mixing procedure. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 1900 rpm for 4 minutes. Add PW80, CB, and SL300 and rapidly mix the mixture at 1900 rpm for 4 minutes. Then degas the final adhesive resin mixture by covering the mixing cup with a polypropylene cap containing a vent hole and mixing under high shear at a reduced pressure of 0.68 psi (approximately 35 torr). The prepared adhesive resin mixtures are individually loaded into 10 sections of a 10:1 dual-syringe dispenser, using an accelerator, trade name “3M SCOTCH-WELD DP8810NS” acrylic adhesive (3M Company), in each case, on one section of the dispenser.
[0170] Table 5: Components of Illustrative Example A
[0171] HEMA 32.78 methacrylic acid 19.31 CLEARSTRENGTH XT100 5.00 BAYMOD N 34.52 2.00 MEHQ 0.05 N+Cl- 0.62 EPX-IEM 24.00 CuNap 0.09 PAM 200 3.11 ESS50F 0.60 HDK H18 2.00 PW80 9.94 CB 0.20 SL300 0.30 total 100.00
[0172] Exemplary Example B
[0173] Exemplary Example B was prepared by combining the components shown in Table 6 in a polypropylene MAX 600 DAC cup (Sonchon Corporation). Each of the material components in each group was rapidly mixed as described. First, hydroxyethyl methacrylate (HEMA), methacrylic acid, lauryl methacrylate, isobornyl methacrylate, benzyl tributylammonium chloride (N+CL-), and methoxyethylhydroquinone (MEHQ) were combined and rapidly mixed at 1500 rpm for 4 minutes using a DAC 400.2VAC (Sonchon Corporation, Landrum, South Carolina). The solid EPX-IEM material was then melted in an oven at 71°C (160℉) for several hours, and the molten material was added to the rapid mixer cup, and the resulting material was rapidly mixed at 2250 rpm for 4 minutes. Then, XT100 was added to the rapid mixer cup, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Baymod rubber material was then added, and the mixture was rapidly mixed at 1900 rpm for 4 minutes. Allow the material to cool for 5 minutes, then rapidly mix at 2250 rpm for 4 minutes. Allow the material to cool for a few more minutes, then rapidly mix at 1900 rpm for 4 minutes. Next, add CuNap, PAM 200, HDK H18, and ESS50F, and rapidly mix the mixture at 1900 rpm for 4 minutes. Next, add PW80, SB, and SL300, and rapidly mix the mixture at 1900 rpm for 4 minutes. After mixing, cool the material in a freezer for 5 minutes. Then add methyl methacrylate, followed by rapid mixing at 2250 rpm for 1 minute. After rapid mixing, degas the final binder resin mixture by covering the mixing cup with a polypropylene cap containing vent holes, and then high-shear mix at a reduced pressure of 0.68 psi (approximately 35 Torr) for 2 minutes. The prepared adhesive resin mixture was individually loaded into 10 sections of a 10:1 dual syringe dispenser, with an accelerator of the acrylic adhesive trade name “3M SCOTCH-WELD DP8810NS” (3M Corporation, St. Paul, Minnesota) used in 1 section of the dispenser in each case.
[0174] Table 6: Illustrative Example B
[0175]
[0176] CB 0.15 SL300 0.34 total 100.00
[0177] result
[0178] The Tg of each cured adhesive was measured using the tanδ peak from DMA analysis, and the Tg data are listed in Table 7.
[0179] Table 7: DMA Tg (tanδ) and % elongation of adhesive formulations
[0180] Exemplary Example A 137-139 21% Exemplary Example B 136-140 16%-18% Example 1 158 6%-8% Example 2 138 51%
[0181] The resulting mixed adhesive was used to prepare overlap shear test specimens on various substrates at various temperatures. All adhesives used for the overlap shear test were prepared by dispensing approximately 0.3 g of the adhesive resin mixture and accelerator resin via a static mixing tip. The overlap shear tests were conducted on untreated nylon 6,6, aluminum, and FR4 glass epoxy resin specimens as described in the above overlap shear tests, in Examples 1, 2, Exemplary Example A (Ill.Ex.A), and Exemplary Example B (Ill.Ex.B), and the results are presented in Tables 8 and 9 below.
[0182] Table 8. Overlapping shear, psi (failure mode) on plastic, metal and composite substrates .
[0183]
[0184] ND = Not measured
[0185] Table 9 .
[0186] Lateral impact at 23C(J) 7.9 8.9 ND Bell peel strength on Al at -40°C 17.7 26.15 2.4 Bell peel strength on Al at 23°C 35.1 32.7 18.0 Bell peel strength on Al at 85°C ND 47.2 ND
[0187] ND = Not measured
[0188] As described in the water immersion overlap shear test, data from two weeks of 60°C water immersion tests on glass fiber epoxy resin substrates for Examples 2, Exemplary Examples A and B, and DP8407 were collected, and the results were the percentage of bond strength retained, which are recorded in Table 10 below.
[0189] Table 10: Two-week 60°C water immersion test - glass fiber epoxy resin (FR4) substrate
[0190]
[0191] ND = Not measured
[0192] A two-week mud application test was conducted on Example 2 and exemplary Examples A and B. The results are shown in Table 11 below.
[0193] Table 11 .
[0194] Exemplary Example A 3% Exemplary Example B 42% Example 2 40%
[0195] The foregoing description, given to enable those skilled in the art to practice this disclosure protected by the claims, should not be construed as a limitation on the scope of this disclosure, which is defined by the claims and all their equivalents.
Claims
1. A composition comprising: Based on the total weight of the acrylic functional compounds in the composition, at least 16% by weight and at most 40% by weight of acrylic monomers comprising cycloalkyl groups having at most 12 carbon atoms; Based on the total weight of the acrylic functional compounds in the composition, 15% to 35% by weight of acrylic monomers containing carboxylic acid groups; Based on the total weight of the acrylic functional compounds in the composition, at least 5% by weight and at most 25% by weight of acrylic monomers containing hydroxyl groups; Based on the total weight of the acrylic functional compounds in the composition, at least 1% and at most 15% by weight of methyl methacrylate; and Based on the total weight of the acrylic functional compounds in the composition, 20% to 40% by weight of a compound comprising a divalent segment L and at least two X groups, wherein the divalent segment L is represented by the following formula: Each of the two-valent segments L is directly bonded to: i) Two secondary N atoms, each of which is directly bonded to another divalent chain segment L or X group. ii) Two tertiary N atoms, each directly bonded to p additional divalent segments L and (2-p) X groups, where p is 0, 1, or 2, or iii) secondary N atoms, which are directly bonded to another divalent chain segment L or X group; and tertiary N atoms, which are directly bonded to p other divalent chain segments L and (2-p) X groups, where p is 0, 1 or 2. Each R 1 Independently representing an alkylene group having 1 to 4 carbon atoms, provided that the R 1 At least some of the groups are -CH2-CH2-CH2-CH2-, where each n independently represents a positive integer, and where each X group is independently represented by the following formula: CH2=C(R)-C(O)-OVWC(O)- Each R is independently hydrogen or methyl, and each W is independently O, S, or NR. 2 , where R 2 It is hydrogen or an alkyl group having up to 4 carbon atoms, and wherein each V is independently an alkylene group optionally inserted with at least one ether or amine bond and optionally substituted with a hydroxyl group.
2. The composition of claim 1, wherein, based on the total weight of the acrylic functional compounds in the composition, the acrylic monomer comprising the carboxylic acid group is present in an amount of at least 20% by weight and at most 35% by weight.
3. The composition of claim 1, wherein the acrylic monomer containing the hydroxyl group is present in an amount of at least 10% by weight and at most 25% by weight, based on the total weight of the acrylic functional compound in the composition.
4. The composition according to claim 1, wherein the compound comprising a divalent segment L and at least two X groups is present in an amount ranging from 20% to 35% by weight, based on the total weight of the acrylic functional compounds in the composition.
5. The composition according to claim 1, wherein the acrylic monomer comprising a cycloalkyl group having at most 12 carbon atoms comprises at least one of isobornyl acrylate or isobornyl methacrylate.
6. The composition according to claim 1, wherein the composition further comprises a toughening agent.
7. The composition according to claim 1, wherein the composition further comprises a filler.
8. The composition according to any one of claims 1 to 7, wherein the composition further comprises a free radical initiator.
9. The composition according to any one of claims 1 to 7, wherein the composition is packaged as a first part of a two-part adhesive composition, wherein the second part comprises a free radical initiator.
10. An adhesive comprising the composition according to any one of claims 1 to 7, the composition being at least partially cured with a free radical initiator, wherein the adhesive composition has a glass transition temperature in the range of 120°C to 180°C.
11. An adhesive comprising the composition according to any one of claims 1 to 7, the composition being at least partially cured with a free radical initiator, wherein the adhesive bonds to at least one polyamide and has an overlap shear strength of at least 1000 psi at room temperature, or bonds to aluminum and has an overlap shear strength of at least 1000 psi at 120°C.
12. An article of manufacture, said article of manufacture bonded using a composition according to any one of claims 1 to 7, said composition being at least partially cured with a free radical initiator, said article of manufacture comprising at least one of a polyamide, a metal or an epoxy resin composite.
13. A method for preparing an adhesive article comprising a first substrate and a second substrate, the method comprising: Combining the composition according to any one of claims 1 to 7 with a free radical initiator to provide an adhesive composition; The adhesive composition is applied to at least one of the first substrate or the second substrate; The adhesive composition is used to adhere the first substrate and the second substrate; as well as The adhesive composition is allowed to cure at least partially in order to prepare the adhesive article.
14. The method of claim 13, wherein at least one of the first substrate or the second substrate comprises at least one of a polyamide, a metal, or an epoxy resin composite material.
Citation Information
Patent Citations
adhesives for dentin
DE4219700A1
1,2,6-Thiadiazine-3,5-dione-1,1 dioxides and their use
EP0059451B1
Two-part adhesive
JP2016155892A
Method for making silicone hydrogel contact lenses
US20120139138A1
Urea-based pressure sensitive adhesives
US20160137893A1